Antidepressant effects of total alkaloids of Fibraurea recisa on improving corticosterone-induced apoptosis of HT-22 cells and chronic unpredictable mild stress-induced depressive-like behaviour in mice - Zhongmei He; He Yu; Hong Wu; Lili Su; Kun Shi; Yan Zhao; Ying Zong; Weijia Chen; Rui Du (Taylor & Francis Group, 2022)
Context Fibraurea recisa Pierre. (Menispermaceae) (FR) is a traditional Chinese medicine known as "Huangteng." The total alkaloids of FR (AFR) are the main active ingredients. However, the pharmacological effects of AFR in the treatment of depression have not been reported.Objectives This study investigates the antidepressant effects of AFR by network pharmacology and verification experiments.Materials and methods Compound-Target-Pathway (C-P-T) network of FR and depression was constructed through network pharmacology. In vitro, HT-22 cells were treated with corticosterone (CORT) solution (0.35 mg/mL), then AFR (0.05 mg/mL) solution and inhibitor AZD6244 (14 μM/mL) or BAY11-7082 (10 μM/mL) were added, respectively. The cell viability was detected by CCK-8. In vivo, C57BL/6 mice were divided into 5 groups, namely the normal group, the CUMS group, the AFR (400 mg/kg) group, and the 2 groups that were simultaneously administered the inhibitory group AZD6244 (8 mg/kg) and BAY11-7082 (5 mg/kg). Western blotting was used to assess the expression level of the proteins.Results AFR could protect HT-22 cells from CORT-induced damage and increase the cell viability from 49.12 ± 3.4% to 87.26 ± 1.5%. Moreover, AFR significantly increased the levels of BDNF (1.3, 1.4-fold), p-ERK (1.4, 1.2-fold) and p-CERB (1.6, 1.3-fold), and decreased the levels of NLRP3 (11.3%, 31.6%), ASC (19.2%, 34.2%) and caspase-1 (18.0%, 27.6%) in HT-22 cells and the hippocampus, respectively.Discussion and conclusions AFR can improve depressive-like behaviours and can develop drugs for depression treatment. Further studies are needed to validate its potential in clinical medicine.